Upaya Peningkatan Hasil Belajar IPA Terpadu Melalui Pendekatan Konstruktivistik SMP Negeri 3 Mandrehe Barat Tahun Pembelajaran 2023/2024 - Esa Doktrin Gulo (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
Low learning outcomes and limited student engagement in Integrated Science learning remained major problems in junior high school classrooms. Learning activities that were still dominated by conventional teaching methods caused students to become passive, less motivated, and experience difficulties in understanding scientific concepts meaningfully. This study aimed to analyze the improvement of learning quality and students’ learning outcomes in Integrated Science through the implementation of a constructivist approach among eighth-grade students at SMP Negeri 3 Mandrehe Barat during the 2023/2024 academic year. The study was conducted using a Classroom Action Research (CAR) design consisting of two cycles involving planning, action, observation, and reflection stages. Data were collected through classroom observations, learning achievement tests, learning quality questionnaires, interviews, and documentation. The findings revealed that the implementation of the constructivist approach improved the quality of the learning process from 67.06% in Cycle I to 92.62% in Cycle II. Students’ average learning outcomes also increased from 68.76 to 82.27, with learning mastery reaching 90.62%. These findings indicate that the constructivist approach was effective in improving student engagement, conceptual understanding, and learning outcomes in Integrated Science learning.